A new HW Vir binary from the Palomar Transient Factory PTF1 J072455.75+125300.3: An eclipsing subdwarf B binary with a M-star companion - Schindewolf, Markus; Levitan, D.; Heber, Ulrich; Drechsel, Horst; Schaffenroth, Veronika; Kupfer, Thomas; Prince, T. (Astronomy & Astrophysics, 2015)
We report the discovery of an eclipsing binary - PTF1 J072456+125301- composed of a subdwarf B (sdB) star (g' = 17.2(m)) with a faint companion. Subdwarf B stars are core helium-burning stars, which can be found on the extreme horizontal branch. About half of them reside in close binary systems, but few are known to be eclipsing, for which fundamental stellar parameters can be derived. We conducted an analysis of photometric data and spectra from the Palomar 60 '' and the 200 '' Hale telescope, respectively. A quantitative spectral analysis found an effective temperature of T-eff = 33 900 +/- 350 K, log g = 5.74 +/- 0.08, and log(n(He)/n(H)) = -2.02 +/- 0.07, typical for an sdB star. The companion does not contribute to the optical light of the system, except through a distinct reflection effect. From the light curve an orbital period of 0.09980(25) d and a system inclination of 83.56 +/- 0.30 degrees were derived. The radial velocity curve yielded an orbital semi-amplitude of K-1 = 95.8 +/- 8.1 km s(-1). The mass for the M-type dwarf companion is 0.155 +/- 0.020 M-circle dot. PTF1 J072456+125301 has similar atmospheric parameters to those of pulsating sdB stars (V346 Hya stars). Therefore it could be a high-priority object for asteroseismology, if pulsations were detected such as in the enigmatic case of NY Vir.
Keywords: binaries: eclipsing; stars: early-type; stars: evolution; stars: fundamental parameters; stars: horizontal-branch; subdwarfs